2021
DOI: 10.4041/kjod.2021.51.6.375
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of the transfer accuracy of a bracket jig fabricated using computer-aided design and manufacturing to the anterior dentition: An in vitro study

Abstract: Objective To evaluate the accuracy of a one-piece bracket jig system fabricated using computer-aided design and manufacturing (CAD/CAM) by employing three-dimensional (3D) digital superimposition. Methods This in vitro study included 226 anterior teeth selected from 20 patients undergoing orthodontic treatment. Bracket position errors from each of the 40 arches were analyzed quantitatively via 3D digital superimposition (best-fit algorithm) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…3D printing technology accurately positioned the brackets by visually accessing the tooth root for virtual placement. Consequently, the total working time of IDB and the number of workers were reduced through automated production [1,14,15] . However, adhesive remains are often left behind when the brackets are glued to the tooth surface of patients with 3D printed guides, causing tooth white spots and bracket loss [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…3D printing technology accurately positioned the brackets by visually accessing the tooth root for virtual placement. Consequently, the total working time of IDB and the number of workers were reduced through automated production [1,14,15] . However, adhesive remains are often left behind when the brackets are glued to the tooth surface of patients with 3D printed guides, causing tooth white spots and bracket loss [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, based on the data, both treatments seemed to be equally effective, but comparatively, OrthGuide was more efficient because it could significantly reduce the time of treatment, thus leading to less [7] found that computer-assisted CAD/CAM bonding had the shortest treatment time (13:8 ± 3:4 months) compared with noncomputerassisted indirect bonding (16:9 ± 4:1 months) and direct bonding (21:9 ± 5:0 months), which was consistent with our findings. After decades of development, computer-assisted indirect bonding has shown advantages in accuracy and tooth movement, for instance, shorter treatment cycles and higher efficiency [19][20][21]. However, the treatment cycle of this technique depends to some extent on whether the patient is at the peak of growth and development and the type and difficulty of malocclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria: (1) caries, (2) implant implantation, (3) poor oral hygiene, (4) dental deformities and quantitative defects, (5) severe tooth displacement hinders the placement of the tray.The sample size was estimated by G*Power (version 3.1.9.4.) according to previous studys [ 4 , 32 , 33 ],with an analysis [90% power (Cohen’s d = 0.5); 5% significance level; Mann-Whitney U tests (two-tailed)]. Therefore, each group should use at least 10 maxillary dental arches to detect the difference between the two methods.…”
Section: Methodsmentioning
confidence: 99%